The Impact of AI- Assisted Learning on Mandarin and English Language Achievement among Indonesian High Schools Students - Mir'ah Azizah; Hasria Riski S (Global Education Journal, 2026)
The rapid development of Artificial Intelligence (AI) has transformed foreign language education by providing innovative learning tools that support language acquisition and learner autonomy. This study aimed to investigate the impact of AI-assisted learning on Mandarin and English language achievement among Indonesian students. A quantitative descriptive design was employed involving 180 senior high school and university students who studied both Mandarin and English as foreign languages. Data were collected through questionnaires, English and Mandarin achievement tests, and students’ academic records. The questionnaire measured students’ frequency of AI use, perceived usefulness of AI tools, and learning motivation. The achievement tests assessed reading, vocabulary, grammar, and writing skills in both languages. The findings revealed that 87% of students regularly used AI-powered applications such as ChatGPT, Grammarly, Google Gemini, and Duolingo. Students who frequently used AI-assisted learning obtained higher average scores in Mandarin (82.4) and English (85.7) compared to students with limited AI usage, whose average scores were 74.1 and 77.3 respectively. Furthermore, 84% of students reported increased learning motivation and 77% reported greater learning autonomy. The results suggest that AI-assisted learning positively influences language achievement, motivation, and engagement in both Mandarin and English language learning contexts. Therefore, integrating AI technologies into foreign language education can enhance learning outcomes and support personalized learning experiences.